2019
DOI: 10.1007/s13205-018-1537-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an estrogen-degrading Pseudomonas putida strain SJTE-1

Abstract: In this report, Pseudomonas putida SJTE1 isolated from an enrichment culture of sludge was confirmed to degrade natural estrogens (17β-estradiol, estrone, estriol), estrogenic chemicals (naphthalene and phenanthrene) and testosterone. The strain completely degraded 1 mg/L 17β-estradiol in 24 h and transformed it into estrone; 90% and 75% of 50 mg/L and 100 mg/L 17β-estradiol were utilized in 7 days, respectively. The transformation efficiency of this strain against natural estrogens was much higher than that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…A total of 6 selected bacteria were screened for their ability to degrade TNT, and these are briefly described in this sub-section. Pseudomonas putida (PS) was a newly isolated strain that exhibited high dioxygenase activity against aromatic compounds, such as estrogen and polycyclic aromatic hydrocarbons (PAHs) [38,39]. Comamonas testosteroni (KF-1), a testosterone degrading bacterium, was obtained from a laboratory-trickling filter that was used to enrich a bacterial community from sewage sludge in the United States [40], while Buttiauxella sp.…”
Section: Selection Of Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 6 selected bacteria were screened for their ability to degrade TNT, and these are briefly described in this sub-section. Pseudomonas putida (PS) was a newly isolated strain that exhibited high dioxygenase activity against aromatic compounds, such as estrogen and polycyclic aromatic hydrocarbons (PAHs) [38,39]. Comamonas testosteroni (KF-1), a testosterone degrading bacterium, was obtained from a laboratory-trickling filter that was used to enrich a bacterial community from sewage sludge in the United States [40], while Buttiauxella sp.…”
Section: Selection Of Bacterial Strainsmentioning
confidence: 99%
“…In the current study, identification of Buttiauxella sp. S19-1 as strong TNT-degrading bacteria suggests enormous potential for cleaning up TNT in marine environments, where this strain was initially isolated [38]. Zhang et al [61] later reported degradation of hormonally active agents by Buttiauxella sp.…”
Section: Gc-ms Analysis Of Adnt Degradation By Buttiauxella Sp S19-1 and Rp34omentioning
confidence: 99%
“…For example, the Sphingomonas strain KC8 was reported as having the capacity to degrade E2, E1 and testosterone, but could not degrade BPA (Roh and Chu 2010). Pseudomonas putida SJTE1 isolated from an enrichment culture of sludge was able to degrade natural estrogens, such as E2, and some estrogenic chemicals but it could not use EE2 or BPA (Wang et al 2019). Pseudomonas putida strain YC-AE1 isolated as a BPA degrader from polluted soil, was able to also degrade related compounds, namely BPS, but was not tested for estrogens (Eltoukhy et al 2020).…”
Section: Biodegradation Assaysmentioning
confidence: 99%
“…DSSKY-A-001, Novosphingobium sp. ES2-1, and L. sphaericus DH-B01, the first step in the degradation of E2 appears to be the oxidation of the C-17 hydroxyl position by an SDR such as 17β-hydroxysteroid dehydrogenase to produce E1 ( Hu et al, 2011 ; Qin et al, 2016 ; Zheng et al, 2016 ; Chen et al, 2017 ; Ye et al, 2017 ; Xiong et al, 2018 , 2020 ; Qiu et al, 2019 ; Wang et al, 2019 ; Wu et al, 2019 ; Wang Y. et al, 2020 ; Li et al, 2021 ). However, there are examples of different E2 degradation pathways reported in bacteria, such as hydroxylation at different positions within different saturated rings (B, C, or D) to produce 4-hydroxyestradiol (4-OH-E2), keto-E1, keto-E2, or E3 ( Xuan et al, 2008 ; Kurisu et al, 2010 ; Yu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%